2021
DOI: 10.1111/appy.12464
|View full text |Cite
|
Sign up to set email alerts
|

Association of FKBP5 gene variants with depression susceptibility: A comprehensive meta‐analysis

Abstract: Background: This comprehensive meta-analysis aimed to combine data from different studies and to estimate the association between FKBP5 polymorphisms and depression.Methods: We performed a meta-analysis of observational studies. An electronic search was conducted on four databases for articles published before July 1, 2020.Results: A total of 5125 patients with depression and 8399 controls from 16 independent studies were included in the analysis. The results showed that FKBP5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…FKBP5 SNPs are highly correlated with depression development and responsiveness to antidepressant drug treatment. Previously, a meta-analysis of 16 independent studies including 5,125 patients with depression and 8,399 controls showed that the FKBP5 rs1360780 and rs4713916 polymorphisms were associated with depression, but there was no significant association for FKBP5 rs9470080 or rs9296158 ( 36 ). FKBP5 rs1360780 T + was significantly correlated with major depression, according to another meta-analysis finding ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FKBP5 SNPs are highly correlated with depression development and responsiveness to antidepressant drug treatment. Previously, a meta-analysis of 16 independent studies including 5,125 patients with depression and 8,399 controls showed that the FKBP5 rs1360780 and rs4713916 polymorphisms were associated with depression, but there was no significant association for FKBP5 rs9470080 or rs9296158 ( 36 ). FKBP5 rs1360780 T + was significantly correlated with major depression, according to another meta-analysis finding ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to trauma, reducing GR sensitivity will impair HPA axis negative feedback, which will lead to an increase in cortisol levels. Cortisol is linked to a variety of stress-related mental disorders, including psychosis ( 31 ), borderline personality disorder ( 32 ), anxiety ( 33 , 34 ), schizophrenia ( 35 ), depression ( 36 , 37 ), PTSD, and suicidal tendencies ( 38 , 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were interviewed by trained interviewers using the Chinese version of the Semi-Structured Assessment for Drug Dependence and Alcoholism (SSADDA). The SSADDA was used to assess a variety of psychiatric disorders, including MAUD 23 , according to the Diagnostic and Statistical Manual of Mental Disorders, 4 th edition (DSM-4); the Chinese version of SSADDA has good reliability and validity in diagnosing MA dependence (according to DSM-4 criteria) and MAUD (according to DSM-5 criteria) 24,25 . We used the DSM-5 criteria in this study.…”
Section: Maud Diagnosis and Symptom Assessmentmentioning
confidence: 99%
“…Since the first report of a significant association of FKBP5 SNPs with depression in 2004, numerous studies have confirmed this association. Recently, a meta-analysis including 16 independent studies further supported FKBP5 polymorphisms as critical risk factors for depression . However, associations of FKBP51 are not exclusive for depression but have also been frequently reported for other stress-related psychiatric disorders, including post-traumatic stress disorder (PTSD), bipolar disorder, and schizophrenia .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a meta-analysis including 16 independent studies further supported FKBP5 polymorphisms as critical risk factors for depression. 14 However, associations of FKBP51 are not exclusive for depression but have also been frequently reported for other stress-related psychiatric disorders, including post-traumatic stress disorder (PTSD), 15 bipolar disorder, 16 and schizophrenia. 17 Interestingly, the increased risk of specific FKBP5 variants for psychiatric disorders is most apparent in interaction with stressful life events, such as childhood maltreatment and trauma.…”
mentioning
confidence: 99%